DESIGN STUDY: INTEGER SUBTRACTION OPERATION TEACHING LEARNING USING MULTIMEDIA IN PRIMARY SCHOOL - Rendi Muhammad Aris; Ratu Ilma Indra Putri; Ely Susanti (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2017)
This study aims to develop a learning trajectory to help students understand concept of subtraction of integers using multimedia in the fourth grade. This study is thematic integrative learning in Curriculum 2013 PMRI based. The method used is design research consists of three stages; preparing for the experiment, design experiment, retrospective analysis. The studied was conducted on 20 students of grade four SDN 1 Muara Batun, OKI. The activities of students in this study consisted of six learning trajectories. The first activity asks the students to classify heroism and non-heroism acts, summarize, and classify integers and non-integer. The second activity asks the students to answer the questions in the film given. The third activity asks students to count the remaining gravel in the film. The fourth activity asks students to count remaining spent money in the film. The fifth activity invites students to play rubber seeds in the bag. The last activity asks students to answer the questions in the student worksheet. The media used along the learning activities are a ruler, rubber seed, student worksheet, money, gravel, and film. The results indicate that the learning trajectory using multimedia help students understand the concept of integer subtraction integer. Keywords: Subtraction Integer, PMRI, MultimediaÂ DOI: http://dx.doi.org/10.22342/jme.8.1.3233.95-102